Reformulated Object Relations Theory: A Bridge Between Clinical Psychoanalysis, Psychotherapy Integration, and the Understanding and Treatment of Suicidal Depression - Shahar, Golan (Frontiers in Psychology, 2021)
In contrast to the fruitful relationship between psychoanalysis/psychoanalysts and the humanities, institutionalized psychoanalysis has been largely resistant to the integration of psychoanalysis with other empirical branches of knowledge (infant observation, psychotherapy research, psychological and neurobiological sciences), as well as clinical ones [primarily cognitive-behavioral therapy (CBT)]. Drawing from two decades of theoretical and empirical work on psychopathology, psychotherapy, and psychoanalysis, the author aims to show how a reformulation of object relations theory (RORT) using (neuro-)psychological science may enhance a clinical-psychoanalytic understanding and treatment of suicidal depression, which constitutes one of the most formidable health challenges of our time. Specifically, he rewrote the notion of Melanie Klein positions—primarily the depressive position—using extant knowledge of structure of emotions, the centrality of mental representations of the future (“prospection”) and the toxic nature of criticism-based emotions. This reformulation enables a dialog between clinical psychoanalysis and other therapeutic schools of thought and sheds light on the understanding and treatment of suicidal depression.